Effects of Incarceration on Criminal Trajectories in the United States, 1994 - Bhati, Avinash Singh ([Verlag nicht ermittelbar], 2007)
Using data from RECIDIVISM OF PRISONERS RELEASED IN 1994: [UNITED STATES] (ICPSR 3355), this study developed an analytical approach to utilize detailed dated criminal arrest history information in order to investigate whether, and to what extent, incarceration is able to deter offenders from future offending. This data collection consists of the syntax for a SAS macro used to estimate individual specific offending micro-trajectories, project counterfactual trajectories, and to assess the actual post-release offending patterns against the backdrop of these counterfactuals. The arrest records of individuals were clustered in chronological order and were truncated after the first post-release re-arrest event. The key independent variables used in estimating the pre-release criminal history accumulation process included the arrest number, the age at first arrest, whether or not the individual was confined as a result of the previous arrest event, and a measure of the number of years taken to reach each arrest event cumulated through the last arrest event. The same set of basic variables were used to model first re-arrest after release (recidivism).